A Higher Order Interpolation Scheme of Finite Volume Method for Compressible Flow on Curvilinear Grids (Communications in Computational Physics, 2020)
A higher order interpolation scheme based on a multi-stage BVD (Boundary Variation Diminishing) algorithm is developed for the FV (Finite Volume) methodon non-uniform, curvilinear structured grids to simulate the compressible turbulentflows. The designed scheme utilizes two types of candidate interpolants includinga higher order linear-weight polynomial as high as eleven and a THINC (Tangent ofHyperbola for INterface Capturing) function with the adaptive steepness. We investigate not only the accuracy but also the efficiency of the methodology through the costefficiency analysis in comparison with well-designed mapped WENO (Weighted Essentially Non-Oscillatory) scheme. Numerical experimentation including benchmarkbroadband turbulence problem as well as real-life wall-bounded turbulent flows hasbeen carried out to demonstrate the potential implementation of the present higherorder interpolation scheme especially in the ILES (Implicit Large Eddy Simulation) ofcompressible turbulence.